Pengaruh Abusive Supervision Terhadap Cyberloafing Melalui Emotional Exhaustion Serta Organizational Commitment Sebagai Moderasi Karyawan Start-Up Milenial Jakarta - Aulia Rahma; Tiarapuspa; Netania Emilisa; Beta Oki Baliartati; Aicha Fatiha Jolie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of Abusive Supervision on Cyberloafing mediated by Emotional Exhaustion and Organizational Commitment as moderators. This study was conducted using a quantitative approach and survey method by taking a sample of 140 respondents from millennial start-up employees in Jakarta with a purposive sampling method. The design in this study was implemented through hypothesis testing. Data collection took place cross-sectionally. The data collection technique used a questionnaire via Google Form. Instrument tests were carried out such as validity and reliability tests, structural equation modeling (SEM) was used to test all hypotheses, descriptive statistical tests using SPSS. The results showed that Abusive Supervision had a positive effect on Cyberloafing, Abusive Supervision had a positive effect on Emotional Exhaustion, In addition, Emotional Exhaustion was able to mediate the effect of Abusive Supervision on Cyberloafing, and Organizational Commitment was able to moderate Emotional Exhaustion on Cyberloafing. The implication is that management needs to focus more on reducing and improving Abusive Supervision, Emotional Exhaustion, Cyberloafing, and Improving Organizational Commitment;